Claiming the wall: How memorial plaques reshape urban landscapes in Russia - Hwang, Kiun (Studia Rossica Posnaniensia, 2024)
This article explores the significance of memorial plaques in Russian cities as sites of history, memory and aesthetics that create a new sensorium of the urban sphere. The plaques, affixed to historic buildings, serve as tangible markers that commemorate significant events and figures from the past. Taking the case of the historic center of St. Petersburg, the article examines how these plaques create a sense of historicity and contribute to the formation of a shared cultural background within the urban sphere. The plaques evolve from simple inscriptions to more elaborate and visually appealing designs. It also highlights the controversies surrounding the selection of individuals to be materialized and remembered and the aesthetic concerns raised by some residents. Meanwhile, the two contemporary projects challenge traditional commemorative practices and their aesthetics: Last Address, which commemorates victims of political repression through individualized plaques, and the Gandhi artist group’s street art interventions. These projects offer alternative approaches to memorialization and engage in dialogue with existing monuments and plaques. These micro-interventions show grassroot resistance within memorializing practices and aesthetics. The article emphasizes the contested nature of public space and the role of memorial plaques in shaping collective memory and historical narratives in Russian cities.